Case report: Advanced breast cancer with scalp metastases: a report of two cases - Yu, Jiaxuan; Yao, Tianze; Zhang, Min; Li, Bingxin (Frontiers in Oncology, 2024)
BackgroundBreast cancer, identified as the most prevalent cancer worldwide, presents considerable difficulties in advanced stages, especially when involving metastatic spread. Scalp metastasis from breast cancer represents a rare and insufficiently explored occurrence. This paper seeks to illuminate this uncommon manifestation by presenting two cases of scalp metastatic breast cancer in Chinese women.Case reportCase 1: A 45-year-old Chinese woman with a history of invasive ductal carcinoma presented with a scalp lesion indicative of recurrence. Concurrently, she was diagnosed with bone metastases and recurrence at the original site. Despite undergoing various treatments, including chemotherapy and hormonal therapy, her condition worsened, ultimately leading to her passing. Case 2: A 40-year-old Chinese woman was initially diagnosed with bilateral breast invasive mucinous carcinoma presenting with bilateral breast masses and a scalp lesion. She also had multiple bone metastases. Following chemotherapy and hormonal therapy, her disease stabilized.ConclusionThese cases of scalp metastatic breast cancer underscore the complexities involved in managing advanced stages of the disease, especially with rare metastatic manifestations. They highlight the importance of comprehensive diagnostic methods, encompassing full-body skin evaluations, and draw attention to the socioeconomic challenges faced in cancer treatment. These findings point to the necessity for more targeted research on uncommon metastatic forms in breast cancer aiming to enhance patient outcomes and refine management approaches.